2018
DOI: 10.1021/acs.inorgchem.8b01380
|View full text |Cite
|
Sign up to set email alerts
|

Structural Diversity and Electronic Properties of 3d Transition Metal Tetraphosphides, TMP4 (TM = V, Cr, Mn, and Fe)

Abstract: Transition-metal (TM) phosphides attract increasing attention with applications for energy conversion and storage, due to their outstanding physical, chemical, and electronic properties. The 3d transition metal tetraphosphides (TMP, TM = V, Cr, Mn, and Fe) possess multiple allotropies and rich electronic properties. Here, we perform the investigations of the structural, electronic, and elastic properties for 3d-TMP (TM = V, Cr, Mn, and Fe) using density functional theory (DFT) calculations. These compounds are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 52 publications
2
30
0
Order By: Relevance
“…The calculated equilibrium lattice parameters, bond lengths, and bond angles for compounds are listed in Table 2 . It is seen that our calculated structural parameters matches well with the reported experimental and calculated data 55 , 58 , 59 .…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…The calculated equilibrium lattice parameters, bond lengths, and bond angles for compounds are listed in Table 2 . It is seen that our calculated structural parameters matches well with the reported experimental and calculated data 55 , 58 , 59 .…”
Section: Resultssupporting
confidence: 86%
“…It is seen that our calculated structural parameters matches well with the reported experimental and calculated data 55 , 58 , 59 .…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…This variation of electronic structure was also observed in other TMP 4 (TM = V, Cr, and Fe) phases, which have the similar crystal structure to MnP 4 . [ 32 ] The electronic structure calculation for TMP 4 (TM = V, Cr, and Fe) indicated that VP 4 showed a continuous band energy indicating the metallic behavior and CrP 4 showed a relatively narrow bandgap of 0.63 eV than that of MnP 4 . On the other hand, three different FeP 4 polymorphs showed the relatively large band gaps of 1.76, 1.83, and 2.13 eV, respectively, with the semiconducting behavior.…”
Section: Resultsmentioning
confidence: 99%